How long is too long? A scoping review of health system delays in lung cancer. (3rd August 2018) - Malalasekera, Ashanya; Nahm, Sharon; Blinman, Prunella L.; Kao, Steven C.; Dhillon, Haryana M.; Vardy, Janette L.
Earlier access to lung cancer specialist (LCS) care improves survival, highlighting the need for streamlined patient referral. International guidelines recommend 14-day maximum time intervals from general practitioner (GP) referral to first LCS appointment ("GP–LCS interval"), and diagnosis to treatment ("treatment interval"). We compared time intervals in lung cancer care against timeframe benchmarks, and explored barriers and facilitators to timely care. We conducted a scoping review of literature from MEDLINE, Embase, Scopus and hand searches. Primary end-points were GP–LCS and treatment intervals. Performance against guidelines and factors responsible for delays were explored. We used descriptive statistics and nonparametric Wilcoxon rank sum tests to compare intervals in studies reporting fast-track interventions. Of 1343 identified studies, 128 full-text articles were eligible. Only 33 (26%) studies reported GP–LCS intervals, with an overall median of 7 days and distributions largely meeting guidelines. Overall, 52 (41%) studies reported treatment intervals, with a median of 27 days, and distributions of times falling short of guidelines. There was no effect of fast-track interventions on reducing time intervals. Lack of symptoms and multiple procedures or specialist visits were suggested causes for delay. Although most patients with lung cancer see a specialist within a reasonable timeframe, treatment commencement is often delayed. There is regional variation in establishing timeliness of care. Delays to lung cancer care occur, especially in secondary care; variation in timeframe guidelines needs addressing http://ow.ly/hZt730kvKAb